HUBUNGAN RASA PERCAYA PADA GURU DENGAN MOTIVASI BELAJAR PADA ANAK JALANAN - Amalina, Cut Dhiya; Mawarpury, Marty; Rachmatan, Risana (Faculty of Psychology, Diponegoro University, 2013)
Street children tend to rule out education due to economic and environmental factors. Role of parents who are not obtained, making the role of the teacher as a substitute which are believed to motivate children to learn. The aim of this study is to measure relationship of trust in teachers with learning motivation on street children. This study used quantitative approach with purposive sampling technique, involving 44 street children from level III in elementary school to level III in senior high school. The study was conducted at UPTD (Regional Technical Unit) Rumoh Seujahtera Aneuk Nanggroe under the auspices of Social Service of Aceh province. Data collection method used is Trust Scale consists of 15 item with reliability of 0.823 and Learning Motivation Scale consists of 18 item with the reliability of 0.780. Methods of analysis using Pearson correlation technique with coefficient correlation r = 0.319 and p <0.035 (p <0,05). The results showed that there is a positive and significant relationship between trust in teachers with learning motivation on street children, thus the higher the trust in the teacher, the better the child’s motivation to learn